STEM-Driven Project Worksheets for Teaching Mathematical Concepts in Differential Equations: Development and Impact through the Aquaponics Context - Rodliyah, Iesyah; Rahmawati, Novia Dwi; Sa'adah, Nihayatus; Saraswati, Sari; Susilo, Claudya Zahrani; Asmarani, Ratih; Khabibah, Siti (Studies in Learning and Teaching, 2025)
This study aimed to develop and evaluate the effectiveness of student worksheets based on Project-Based Learning (PjBL) integrated with the STEM approach in the context of mathematical aquaponics for an Ordinary Differential Equations course. The research employed a mixed-methods design using the ADDIE development model, with a quantitative approach through pretest and posttest evaluations and a qualitative approach through observations and a student response questionnaire. Expert validation results indicate that the developed worksheets achieved a high level of validity in terms of content, structure, and language. The implementation of the worksheets involved 10 fourth-semester students of the Mathematics Education program at Hasyim Asy’ari University. Statistical test results show a significant improvement in student learning outcomes after using the STEM-PjBL-based worksheets, with a significance value more than 0.05. Additionally, 88.89% of students gave positive responses to the worksheets, particularly in the aspects of learning motivation, active engagement, and contextual understanding of concepts. These findings indicate that the integration of STEM with PjBL in worksheets within the aquaponic context is effective in improving learning outcomes, critical thinking skills, and student engagement in meaningful mathematics learning.